Mucosal immunity of mannose-modified chitosan microspheres loaded with the nontyepable Haemophilus influenzae outer membrane protein P6 in BALB/c mice - Ma, Yushuai; Zhao, Ying; Chen, Rui; Sun, Wanru; Zhang, Yanxia; Qiao, Haixia; Chang, Yueli; Kang, Shaoping; Zhang, Yutuo (PloS one, 2022)
Nontypeable Haemophilus influenzae (NTHi) is a common opportunistic pathogen that colonizes the nasopharynx. NTHi infections result in enormous global morbidity in two clinical settings: otitis media in children and acute exacerbation of chronic obstructive pulmonary disease (COPD) in adults. Thus, there is an urgent need to design and develop effective vaccines to prevent morbidity and reduce antibiotic use. The NTHi outer membrane protein P6, a potential vaccine candidate, is highly conserved and effectively induces protective immunity. Here, to enhance mucosal immune responses, P6-loaded mannose-modified chitosan (MC) microspheres (P6-MCMs) were developed for mucosal delivery. MC (18.75%) was synthesized by the reductive amination reaction method using sodium cyanoborohydride (NaBH 3 CN), and P6-MCMs with an average size of 590.4±16.2 nm were successfully prepared via the tripolyphosphate (TPP) ionotropic gelation process. After intranasal immunization with P6-MCMs, evaluation of humoral immune responses indicated that P6-MCMs enhance both systemic and mucosal immune responses. Evaluation of cellular immune responses indicated that P6-MCMs enhance cellular immunity and trigger a mixed Th1/Th2-type immune response. Importantly, P6-MCMs also trigger a Th17-type immune response. They are effective in promoting lymphocyte proliferation and differentiation without toxicity in vitro. The results also demonstrate that P6-MCMs can effectively induce MHC class I- and II-restricted cross-presentation, promoting CD4 + -mediated Th immune responses and CD8 + -mediated cytotoxic T lymphocyte (CTL) immune responses. Evaluation of protective immunity indicated that immunization with P6-MCMs can reduce inflammation in the nasal mucosa and the lung and prevent NTHi infection. In conclusion, MCMs are a promising adjuvant-delivery system for vaccines against NTHi.